PENGARUH PENDIDIKAN AGAMA ISLAM TERHADAP TINGKAH LAKU SISWA: SDN TAMBELANG I DESA TAMBELANG KRUCIL - MUHYI MUHYI (Dewan Pendidikan Bondowoso, 2022)
SDN Tambelang I Tambelang Krucil village is an Islamic educational institution that is expected to be able to produce the seeds of a Muslim generation who can carry out Islamic religious orders properly and correctly, from which learning processes must be built in the classroom and outside the classroom that can shape students' morals. and students with good morals. good. This study also aims to find out how much influence the role of Islamic religious education learned in school has on the morals of students at SDN Tambelang I, Tambelang Krucil village and to find out what efforts are being made by schools to improve the morals of students at SDN Tambelang I, Tambelang Krucil village. This research method uses a qualitative descriptive method using a case study. The result of this study is that there is a change in the morals of students at SDN Tambelang I, Tambelang Krucil village